Carrizo citrange Plants Do Not Require the Presence of Roots to Modulate the Response to Osmotic Stress - Rosa M. Pérez-Clemente; Almudena Montoliu; Sara I. Zandalinas; Carlos de Ollas; Aurelio Gómez-Cadenas (The Scientific World Journal)
The study of the effects of a specific stress condition on the performance of plants grown under field conditions is difficult due to interactions among multiple abiotic and biotic factors affecting the system. In vitro tissue-culture-based techniques allow the study of each adverse condition independently and also make possible to investigate the performance of genotypes of interest under stress conditions avoiding the effect of the root. In this paper, the response of Carrizo citrange, a commercial citrus rootstock, to osmotic stress was evaluated by culturing in vitro intact plants and micropropagated shoots. The osmotic stress was generated by adding two different concentrations of polyethyleneglycol to the culture media. Different parameters such as plant performance, organ length, antioxidant activities, and endogenous contents of proline, malondialdehyde, and hormones were determined. Differently to that observed under high salinity, when subjected to osmotic stress conditions, Carrizo citrange showed increased endogenous levels of MDA, proline, and ABA. These results evidence that the mechanisms of response of Carrizo citrange to saline or osmotic stress are different. The presence of roots was not necessary to activate any of the plant responses which indicates that the organs involved in the stress perception and signaling depends on the type of adverse condition to which plants are subjected.